2022
DOI: 10.3390/ijms23147594
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Predictors of Lung-Cancer Resistance and Sensitivity to Cisplatin

Abstract: Background: Platinum-based chemotherapy, cisplatin (DDP) specifically, is the main strategy for treating lung cancer (LC). However, currently, there is a lack of predictive drug-resistance markers, and there is increased interest in the development of a reliable and sensitive panels of markers for DDP chemotherapy-effectiveness prediction. MicroRNAs represent a perspective pool of markers for chemotherapy effectiveness. Objectives: Data on miRNAs associated with LC DDP chemotherapy response are summarized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 192 publications
0
6
0
Order By: Relevance
“…Increasing evidence suggests that miRNAs play a vital role in tumor development and metastasis by suppressing downstream gene expression. [19,20] Studies have detected changes in miRNA levels in the tissues, organs, secretions, and peripheral blood of patients with lung tumors. A ten-year cohort study revealed high expression of serum miRNAs during lung cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that miRNAs play a vital role in tumor development and metastasis by suppressing downstream gene expression. [19,20] Studies have detected changes in miRNA levels in the tissues, organs, secretions, and peripheral blood of patients with lung tumors. A ten-year cohort study revealed high expression of serum miRNAs during lung cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA are short 20-22 nucleotide RNA sequences that upon binding to complementary regions (seeds) on target mRNA molecules affect their transcription leading in the majority of cases to its inhibition by inducing RNA degradation or inhibiting its translation. Sequencing of patients derived material highlighted multiple miRNA, which could serve as prognostic markers and/or predict treatment response, for example to radiotherapy (RT) and/or tamoxifen in BC patients ( 37 ), to RT in prostate cancer ( 38 ) and to cisplatin in lung cancer ( 39 ).…”
Section: Search For Biomarkers For Patient Stratificationmentioning
confidence: 99%
“…Used often in conjunction with drugs like paclitaxel and gemcitabine, as well as radiotherapy, cisplatin faces the signi cant hurdle of drug resistance, which undermines its effectiveness [8]. The exploration of cisplatin chemoresistance mechanisms and the search for molecular markers for early diagnosis, survival prediction, and relapse monitoring in LUAD are thus of paramount importance [9,10]. In this context, bioinformatics emerges as a crucial tool in unraveling the molecular intricacies of LUAD progression and identifying potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%